PROBLEMATIKA PENDIDIKAN KARAKTER PENDIDIKAN TINGGI - Choli, Ifham (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2020)
Character education in higher education aims to improve the quality of implementation and educational outcomes that lead to the achievement of the formation of the character and noble character of students as a whole, integrated and balanced according to graduate competency standards. Through character education, students are expected to be able to independently improve and use their knowledge, study and internalize character values ​​so that they are manifested in daily behavior. The implementation of character education has its own problems, namely the existence of unsynchronization between the concepts of character education, which aims to restore the culture and character of the nation which is increasingly deteriorating with the reality faced. Character education in higher education is everything done by a lecturer, able to influence the character of students. This includes many things about the exemplary of a lecturer be it behavior, speech, tolerance, integrity and others related to character. The campus environment as an escort institution for character building for students, has potentials that will contribute to the processes, so synergy is needed together in coaching from all campus residents. In teaching character building, lecturers can integrate it naturally with the standard curriculum or teach it in tandem with the standard curriculum. All lecturers in all subjects should be figures who practice the formation of this character in all activities in the classroom and outside the classroom.